Spray with Nitric Oxide Donor Accelerates Wound Healing: Potential Off-the-Shelf Solution for Therapy? - Igrunkova A; Fayzullin A; Churbanov S; Shevchenko P; Serejnikova N; Chepelova N; Pahomov D; Blinova E; Mikaelyan K; Zaborova V; Gurevich K; Urakov A; et al. (Dove Medical Press, 2022)
Alexandra Igrunkova,1,2 Alexey Fayzullin,1,2 Semyon Churbanov,1 Polina Shevchenko,1 Natalia Serejnikova,1,2 Natalia Chepelova,1,2 Dmitry Pahomov,3 Ekaterina Blinova,4 Karen Mikaelyan,1 Victoria Zaborova,5,6 Konstantin Gurevich,7 Aleksandr Urakov,8,9 Anatoly Vanin,1 Peter Timashev,1,2,10 Anatoly Shekhter1 1Institute for Regenerative Medicine, Sechenov First Moscow State Medical University, Moscow, Russian Federation; 2World-Class Research Center "Digital Biodesign and Personalized Healthcare", Sechenov First Moscow State Medical University, Moscow, Russian Federation; 3Department of Operative Surgery and Topographic Anatomy, Sechenov First Moscow State Medical University, Moscow, Russian Federation; 4Department of Faculty Surgery, Ogarev Mordovia State University, Saransk, Republic of Mordovia, Russian Federation; 5Institute of Clinical Medicine, Sechenov First Moscow State Medical University, Moscow, Russian Federation; 6Laboratory of Sports Adaptology, Moscow Institute of Physics and Technology, Dolgoprudny, Moscow Region, Russian Federation; 7UNESCO Chair "Healthy life style for sustainable development", Moscow State University of Medicine and Dentistry, Moscow, Russian Federation; 8Department of General and Clinical Pharmacology, Izhevsk State Medical Academy, Izhevsk City, Udmurt Republic, Russian Federation; 9Department of Modeling and Synthesis of Technological Processes, Institute of Applied Mechanics, Udmurt Federal Research Center of the Ural Branch of the Russian Academy of Sciences, Izhevsk City, Udmurt Republic, Russian Federation; 10Department of Chemistry, Lomonosov Moscow State University, Moscow, Russian FederationCorrespondence: Aleksandr Urakov, Department of General and Clinical Pharmacology, Izhevsk State Medical Academy, Kommunarov str., 281, Izhevsk City, Udmurt Republic, 426034, Russian Federation, Tel +011 79127600939, Email urakoval@live.ruBackground: Ditrosyl iron complexes (DNIC) are endogenous donors of nitric oxide. The possibility of their application to stimulate regeneration has been studied for more than 15 years. However, the most effective dose and form of delivery have not yet been determined.Purpose: The aim of this research was to develop a spray form of DNIC that accelerates wound healing.Methods: We prepared a series of DNIC sprays with spray dosages of 10, 50 and 100 μg. We modelled full-thickness skin wounds in 24 Wistar rats and treated them with distilled water (n = 6), 10 (n = 6), 50 (n = 6) and 100 μg (n = 6) for three post-operative days. On the fourth day, the excised wound tissues were studied by morphological, immunohistochemical and morphometric methods.Results: We demonstrated that 50 μg of DNIC spray had the most beneficial effect on wound healing: the thickness of the granulation tissue layer was 140% higher, vimentin positive fibroblasts predominated and the intensity of inflammation was significantly lower than in the control. There was a dose-dependent decrease in the functional activity of mast cells in the experimental groups compared to the control.Conclusion: DNIC spray is a potential effective dosage form for the treatment of large-area skin lesions.Graphical Abstract: Keywords: wound, infection, drug, resistance, research and development, nitric oxide, spray, healing